Monopolistic Competition and the Stability Conditions - Reder, M. W. (Review of Economic Studies, 1941)
Monopolistic Competition and the Stability Conditions Get access M. W. Reder M. W. Reder Chicago, Illinois, U.S.A. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 8, Issue 2, February 1941, Pages 122–125, https://doi.org/10.2307/2967469 Published: 01 February 1941